The association between material hardship and physical and mental health among older adults: Multi-channel sequence Approach - Oejin Shin; Eunsun Kwon; Seoyeon Ahn; Sojung Park (PLoS ONE, 2025)
Older adults often face financial difficulties due to declining physical and cognitive abilities, and rising healthcare costs exacerbate these issues. Despite a general decrease in poverty, the rate among those aged 65 and older has increased. Material hardship is particularly relevant for older adults due to their complex healthcare needs. However, research on long-term material hardship patterns among older adults is limited and often focuses on only a few dimensions of hardship. This study aims to explore the long-term patterns of material hardship and their impact on well-being using data from the Health and Retirement Study. Employing multi-channel sequence analysis, we model various material hardship trajectories and examine their association with mental and physical health. Five distinct patterns of material hardship were identified, with the Multiply burdened group experiencing the most severe hardships, often linked to females, low education, and poverty. The findings highlight the significant negative effects of persistent material hardship on health, emphasizing the need for targeted policies and support programs to address the unique challenges faced by older adults, especially those related to housing and financial stress.